Seasonal variation of foraging niches in a guild of passerine birds in a cork-oak woodland - Almeida, J.; Granadeiro, J. P. (ARDEA, 2000)
Spatial foraging niches of a pariform guild in a cork-oak woodland were examined during winter and spring. Niche structure was described in terms of the niche dimensions foraging substrate, foraging height and part of tree, and seasonal changes in niche breadth and overlap were examined. Considering the difficulties of dealing with the multidimensionality of Hutchinson's niche concept, we adopted a multivariate approach and identified the most important factors for spatial segregation. Significant differences between winter and spring utilisation of the foraging dimensions were found for the guild as a whole. At the species level, however, no major seasonal differences in the utilisation of foraging dimensions were found. No consistent seasonal trend occurred in terms of niche size or niche overlap. Multivariate analysis showed that the guild structure is basically the same in winter or spring, with Little influence of species that are present in only one of the two seasons. These results suggest that there is no food shortage in winter for the pariform guild in this woodland. The niche dimensions related with tree structure and foraging substrate appeared to be the most important ones in species segregation.
The following values have no corresponding Zotero field: pub-location: C/O PAUL STARMANS, OUDE ARNHEMSEWEG 261, 3705 BD ZEIST, NETHERLANDS publisher: NEDERLANDSE ORNITHOLOGISCHE UNIE
Keywords: community ecology; cork-oak woodland; guild; niche; passerines